Efficacy of microsurgery in combined with topical-PDT in treating recurrent respiratory papillomatosis: compare JORRP with AORRP. (2nd December 2019) - Yang, Shuzhi; Zhou, Chengyong; Sun, Baochun; Wang, Feng; Han, Zeli; Zhang, Hongjia; Han, Jiahong; Shen, Yao; Zhang, Jiao
Abstract: Background: Recurrent respiratory papillomatosis (RRP) remains a challenging and frustrating disease to treat. Objective: To explore the efficacy of microsurgery in combined with Topical-PDT in treating recurrent respiratory papillomatosis. Materials and methods: Fifty patients with RRP were treated with microsurgery in combined with Topical-PDT. Medical document of each patient was retrospectively reviewed. Detailed clinical information, metrics of clinical course, and current results were evaluated. Results: Juvenile onset RRP (JORRP) might experience a more aggressive course than AORRP (adult onset RRP) with higher Derkay score ( p  < .01) and higher operation frequency per year ( p  < .01). Microsurgical excision combined with Topical-PDT every 25 days achieved "remission" of disease in 78% of patients, "clearance" of disease in 52%, and "Cured" in two patients. Each patient who achieved "remission" of disease, performed 6.82 ± 3.39 operations, and continued 8.93 ± 7.03 months of treatment duration. No statistically differences were found in these two aspects between JORRP and AORRP. A negative correlation between tracheotomy and the efficacy of microsurgery in combined with Topical-PDT was found ( p  = .025, Pearson's r = –0.3). Conclusions and significance: Microsurgery in combined with Topical-PDT might be a powerful method to treat RRP. Tracheotomy is a negative factor for this therapy.